Diplomat sebagai Pegawai Negeri Sipil - Abdurrahman Al-Fatih Ifdal (Jurnal Manajemen Kepegawaian, 2023)
International diplomatic practice in international law directly influences the regulatory structure of diplomatic agents’ governance, including Indonesian diplomats who are categorized as officials with a functional status according to Indonesian civil service administration law. Functionality and state civil servants elements that bind Indonesian diplomats can hinder adjustments occuring in the order of international diplomatic practice. This article aims to analyze how Indonesia’s national legal regime can accommodate a resolution on legal vacuum or legal imbalance cases that befalls Indonesian diplomats in the context of the intersection of international diplomatic law provisions and Indonesian laws on civil service administration law and government bureaucracy. The method used in this research is a thematic analysis approach to an in-depth study of the norms that develop in international courts that question the position of a diplomat as studied in international law. The results of this research indicate that there needs to be more authority for the Ministry of Foreign Affairs of the Republic of Indonesia to be able to fabricate innovative mechanisms in adopting developed diplomatic practice norms among states, not only limited to amendments to legal products, in order to cater the developments in international diplomatic practice norms.